Effect of the bed bath on cardiac output - Laferriere, Joan Edna (Boston University, 2019)
Thesis (M.S.)--Boston University === PLEASE NOTE: Boston University Libraries did not receive an Authorization To Manage form for this thesis or dissertation. It is therefore not openly accessible, though it may be available by request. If you are the author or principal advisor of this work and would like to request open access for it, please contact us at open-help@bu.edu. Thank you. === 2031-01-01